Granular swollen epithelial cells in the kidney allograft: A clinicopathological study with special emphasis on possible marker for kidney allograft aging. (July 2016) - Hara, Shigeo; Ishimura, Takeshi; Fujisawa, Masato; Nishi, Shinichi; Itoh, Tomoo
Abstract: Aim: To elucidate the clinicopathological significance of granular swollen epithelial cells (GSECs), which provides histological evidence in the diagnosis of mitochondrial nephropathy, but incidentally observed in renal allografts, we evaluated GSECs as a surrogate histological marker for kidney allograft aging, as previously reported for p16, p21, and β‐galactosidase. Methods: We retrospectively reviewed 426 kidney allograft biopsy specimens diagnosed at our university from January 2009 to April 2015. The prevalence and density of GSECs were compared with an age‐matched control group of 508 native kidney biopsies. GSECs were defined as swollen (>2 times larger than normal renal tubular cells) epithelial cells best observed using Masson trichrome staining. Morphometric analyses were performed using digital microscopy software. Results: The prevalence of GSECs was 7.7% in allograft kidneys and 8.1% in native kidneys. GSECs in kidney allografts were predominantly detected in medullary renal tubules, but not in the Bowman's capsular epithelium or podocytes. GSECs were observed in the following cases; no remarkable changes, n = 11; interstitial fibrosis and tubular atrophy, n = 7; chronic calcineurin inhibitor toxicity, n = 5; antibody‐mediated rejection, n = 3; T cell‐mediated rejection grade IA, n = 1; and others, n = 6. Compared with control specimens, medullary density of GSECs in kidney allografts was significantly increased. The prevalence of GSECs slightly increased with post‐transplant duration; however, this trend was not statistically significant. Conclusions: The present study does not provide pathological significance of GSEC in kidney allografts in terms of allograft aging, and warrant the further research with molecular approach.